Brief Report: Refusal of Daily Oral PrEP: Implementation Considerations and Reported Likelihood of Using Various HIV Prophylaxis Products in a Diverse Sample of MSM. (1st March 2023) - Mansergh, Gordon; Kota, Krishna Kiran; Carnes, Neal; Gelaude, Deborah
Abstract : Background: An important subgroup of gay, bisexual, and other men who have sex with men (MSM) with behavioral indications refuse daily oral pre-exposure prophylaxis (PrEP) when recommended by a provider. Emerging HIV prophylaxis products (eg, injectable, event-driven) offer more options to MSM who refuse daily PrEP. In this article, we assess reasons for refusal and likelihood to use various products among MSM who refused PrEP. Methods: MSM who reported anal sex without condoms or PrEP and refused daily oral PrEP in the past 6 months were recruited through clinics, community venues, and online in Atlanta, Chicago, and Raleigh-Durham. Men were asked their main reason for recently refusing daily PrEP and likelihood of using various PrEP options in the future. Bivariate and multivariable regression models were used to estimate associations. Results: MSM (n = 93; 70% Black, 48% age 18–29 years) reported their main reason for refusing daily PrEP were potential side effects (35%), a daily pill regimen (22%), and not having enough information (18%). Reported likelihood of using PrEP products was 58% for penile gel, 54% for event-driven oral, 52% for injectable, and 50% for daily PrEP. MSM who reported daily regimen as the main reason for refusing PrEP had greater odds of likelihood to use an injectable [adjusted odds ratio (AOR) = 5.21, 95% confidence interval (CI): 1.32 to 20.52]. Younger men (18–29 vs 30+ years) had greater odds of likelihood to use condoms (AOR = 3.40, 95% CI: 1.15 to 10.04) and daily PrEP (AOR = 2.76, 95% CI: 1.06 to 7.16); there were no product preference differences by race. Conclusion: Most men who refused daily PrEP indicated likelihood of using some form of PrEP in the future.